Hubungan Krisis identitas dengan kedisiplinan siswa di SMK Negeri 4 Tanjung Jabung Timur - Kurnia, Dewi; Rasimin, Rasimin; Harahap, Nur Hasanah (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2024)
This research is motivated by student discipline where students commit disciplinary violations at school. This research aims and focuses on revealing the relationship between identity crisis and student discipline at SMK Negeri 4 Tanjung Jabung Timur. This type of research is quantitative research with correlation methods. The population in this study were all students at SMK Negeri 4 Tanjung Jabung Timur for the 2023-2024 academic year. The sample in this research was 96 students using the purposive sampling technique. The instrument used is a questionnaire (Questionnaire). Data analysis uses the Percentage Test with formula C, Normality Test, Linearity Test and Correlation Test. The research results show that: the level of identity crisis for students at SMK Negeri 4 Tanjung Jabung Timur is in the high category with a percentage of 73%. The level of student discipline at SMK Negeri 4 Tanjung Jabung Timur is in the high category with a percentage of 75%. The Pearson correlation value obtained is interpreted using correlation guidelines, where the calculated r (0.662) is in the range (0.40-0.70) which is interpreted as being in the medium category. It can be concluded that there is a significant relationship between identity crisis and student discipline. From the research results, it is recommended that future researchers be able to use other research methods to strengthen the validity of the research and that future researchers can improve this research by reducing errors in research.